Una & Miguel - Bose, Lilledeshan; Quibilan, Sunantha Mendoza (Adarna House, Inc., 2002)
For these two, love is truly a long shot. But when they're forced to work together as punishment for a prank-gone-wrong, they find that falling in love might not be so impossible after all. Will opposites attract? Or will they repel?.